Health Status of Minority Francophone Seniors in Manitoba and Access to Services in French: Potential for Social Isolation - de Moissac, Danielle; Roch-Gagné, Margaux; Ba, Halimatou; Gueye, Ndèye Rokhaya; Ether, Sophie (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2016)
Francophone seniors in Manitoba represent a growing and vulnerable population, with poorer health outcomes and limited access to health and social services in the official minority language. To avoid isolation, support services are required, as chronic diseases and reduced mobility have a direct impact on both physical and social needs. The purpose of this study is to examine the current health status of seniors in the Francophone minority population of Manitoba and their access to health and social services in French. Demographic, social and health profiles were obtained for Francophone and non-Francophone Home Care clients in Winnipeg. Although diagnosed with similar health conditions as non-Francophones, Francophone seniors are less likely to be assessed with reduced cognitive performance and conditions making mood and behaviour unstable, such as dementia other than Alzheimer’s. Gaps in bilingual health services were identified for pharmacy, audiology and occupational therapy services, meal and transportation systems as well as support services for informal caregivers. Housing options with in-house support services provided in French are available and additionally provide opportunities for seniors to socialize with other Francophones. For the elderly living in singlehome units and their caregivers, support services provided in the official minority language are needed.